Tula Basin, the most polluted region in Mexico - Díaz-Quiñonez, José Alberto (Mexican Journal of Medical Research ICSA, 2023)
Tenochtitlan was founded in an endorheic basin at more than two thousand meters of altitude, surrounded by mountains in the lacustrine river basin of the Valley of Mexico. I ts geographical location explains the water vulnerability of the current Metropolitan Area of the Valley of Mexico (MAVM).